Penilaian Kinerja Keuangan Menggunakan Metode Economic Value Added pada PT Nippon Indosari Corpindo Tbk - Cantik Wiradinda Suhud; Djoni Djatnika; Dimas Sumitra Danisworo (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this paper is to measure financial performance with the Economic Value Added (EVA) method at PT Nippon Indosari Corpindo Tbk period 2014-2018. The datas which writer used in writing this final report is secondary data in the statement of financial position and statement of profit or loss period 2014-2018, general history corporate and data collection method used is documentation technique. This company has not used Economic Value Added (EVA) Method in assessing its financial performance. Based on the results of the analysis and calculations the writer, the financial performance of PT Nippon Indosari Corpindo Tbk. if using Economic Value Added (EVA) method during the year 2014-2018 has not been good with marked value negative EVA or EVA < 0 every year. Its means the company has not succeded to increase the economic value added and not capable to generate the expected returns by shareholders on the investments that has been undertakes.